Hubungan Ecoliteracy dengan Sikap Peduli Lingkungan Peserta Didik di Sekolah Dasar Adiwiyata Kecamatan Banjarsari - A'yuninnata, Kumala; Saputri, Dwi Yuniasih (Universitas Sebelas Maret, 2026)
This study examines the relationship between ecoliteracy and environmental awareness in elementary school students at Adiwiyata schools in Banjarsari District. This study uses a quantitative research type with a correlational design, focusing on the relationship between ecoliteracy (X) and environmental awareness (Y). The research sample was 4 adiwiyata elementary schools with 88 students. Data collection used scales and data analysis used prerequisite tests and hypothesis testing. The results of this study are that there is a simultaneous relationship between ecoliteracy and environmental care attitudes, with a significance value of 0.000 <0.05 with a Pearson correlation value of 0.589 in the moderate category. The results showed a significant positive correlation between ecoliteracy and environmental awareness. Ecoliteracy improves individuals' understanding of ecological concepts and their ability to overcome environmental problems, thereby fostering proactive behavior towards sustainability.